Analisis Motivasi Kinerja Guru SDK Kalena Wanno - Irfandi L. Talu; Elfrida S. Tanggu; Emiliana Kaka; Marselina A. Bangga (Pusat Riset dan Inovasi Nasional, 2024)
In the era of globalization, education has a very important role in all aspects of humanity. The aim of this research is to find out whether there is a Motivational Analysis of the Performance of SDK KALENA WANNO Teachers. The method used in this research is descriptive research method. Results: Research conducted at SDK Kelana Wanno in May 2024. The research subjects were SDK Kelana Wanno teachers. Conclusion The motivation of SDK Kelana Wanno teachers is mostly in the good category. In the era of globalization, education has a very important role in all aspects of humanity. The purpose of this research is to determine whether there is a Motivational Analysis of the Performance of SDK KALENA WANNO Teachers. The method used in this research is descriptive research method. Results: The research was conducted at SDK Kelana Wanno in May 2024. The research subjects were SDK Kelana Wanno teachers. Conclusion The motivation of SDK Kelana Wanno teachers is mostly in the good category.